Diagnóstico del Uso de Herramientas Tecnológicas para la Gestión y Apoyo del Liderazgo en las PYMES (2019)
The purpose of this article is to show the result of the diagnosis of the use of the Technological Tools (TH) for the management and support of small and medium-sized enterprises (SMEs) in the Xalapa region, Veracruz México, aiming to point out the relevance of this technology since in recent years it has been demonstrated that organizations of all types and sizes require a significant change in the focus of their own management, which requires the incorporation of Information Technologies, the study was conducted based on A sample of companies applying an instrument that collected data on leaders and followers, evaluating how many of them use technological tools and what they contribute to improving their leadership activities, in order to persuade their collaborators by promoting work in equipment to achieve the objectives of the company. Understanding its importance in the organizational environment, the theories of leadership are analyzed identifying their characteristics, attitudes and actions relevant to improving their performance. However, the use of the TH has been little used in such a way that knowledge about leadership is not enough to exercise it, it is necessary to use the technology to improve it.